Parent-led cognitive behaviour therapy for child anxiety problems: overcoming challenges to increase access to effective treatment - Creswell, C; Chessell, C; Halliday, G (Cambridge University Press, 2022)
Background: Anxiety problems have a particularly early age of onset and are common among children. As we celebrate the anniversary of the BABCP, it is important to recognise the huge contribution that cognitive behavioural therapy (CBT) has made to the treatment of anxiety problems in children. CBT remains the only psychological intervention for child anxiety problems with a robust evidence base, but despite this, very few children with anxiety problems access CBT. Creative solutions are urgently needed to ensure that effective treatments can be delivered at scale. Here we focus on parent-led CBT as this offers a potential solution that is brief and can be delivered by clinicians without highly specialised training. Over the last decade there has been a substantial increase in randomised controlled trials evaluating this approach with consistent evidence of effectiveness. Nonetheless clinicians, and parents, often have concerns about trying the approach and can face challenges in its delivery.